Non Conviction Base (NCB) Asset Forfeiture Regarding the Recovery of Assets from the Proceeds of Corruption Crimes - Hasibuan, H. A. Lawali (Civiliza Publishing, 2025)
Non-Conviction Based Asset Forfeitureas a new formulation in efforts to return assets resulting from corruption crimes can be adopted into the Indonesian national legal systemas an effort to restore state losses to the maximum. The state losses that have been returned are still not comparable to the state losses that actually exist due to corruption.The research method used is normative juridical law or library legal research (search library), by analyzing literature or secondary data relevant to the topic. This research is descriptive analytical, the data obtained and processed and analyzed to provide a comprehensive picture of the legal regulations on Non Conviction Base (NCB) Asset Forfeiture against the Asset Confiscation Bill with data collection methods through document studies. The results of the study show that asset confiscation without criminalization orNon-Conviction Based Asset Forfeitureis a major breakthrough regarding the return of state wealth (asset recovery) issued by UNCAC in 2003. The conceptNCB Asset Forfeiturein essence is the seizure of assets from the perpetrator of a crime without any prior legal process. So in this case, the seizure is carried out in a civil manner (in brake) and is aimed at the perpetrator's assets without going through a criminal process.